Peritoneal dialysis in rural Australia - Gray, Nicholas A (BioMed Central, 2013)
BACKGROUND: Australians living in rural areas have lower incidence rates of renal replacement therapy and poorer dialysis survival compared with urban dwellers. This study compares peritoneal dialysis (PD) patient characteristics and outcomes in rural and urban Australia. METHODS: Non-indigenous Australian adults who commenced chronic dialysis between 1 January 2000 and 31 December 2010 according to the Australia and New Zealand Dialysis and Transplant Registry (ANZDATA) were investigated. Each patient’s residence was classified according to the Australian Bureau of Statistics remote area index as major city (MC), inner regional (IR), outer regional (OR), or remote/very remote (REM). RESULTS: A total of 7657 patients underwent PD treatment during the study period. Patient distribution was 69.0% MC, 19.6% IR, 9.5% OR, and 1.8% REM. PD uptake increased with increasing remoteness. Compared with MC, sub-hazard ratios [95% confidence intervals] for commencing PD were 1.70 [1.61-1.79] IR, 2.01 [1.87-2.16] OR, and 2.60 [2.21-3.06] REM. During the first 6 months of PD, technique failure was less likely outside MC (sub-hazard ratio 0.47 [95% CI: 0.35-0.62], P < 0.001), but no difference was seen after 6 months (sub-hazard ratio 1.05 [95% CI: 0.84-1.32], P = 0.6). Technique failure due to technical (sub-hazard ratio 0.57 [95% CI: 0.38-0.84], P = 0.005) and non-medical causes (sub-hazard ratio 0.52 [95% CI: 0.31-0.87], P = 0.01) was less likely outside MC. Time to first peritonitis episode was not associated with remoteness (P = 0.8). Patient survival while on PD or within 90 days of stopping PD did not differ by region (P = 0.2). CONCLUSIONS: PD uptake increases with increasing remoteness. In rural areas, PD technique failure is less likely during the first 6 months and time to first peritonitis is comparable to urban areas. Mortality while on PD does not differ by region. PD is therefore a good dialysis modality choice for rural patients in Australia.